Mulher, mercado de trabalho e as configurações do seculo XX - Simões, Fátima Itsue Watanabe; Hashimoto, Francisco [UNESP] (My University, 2012)
The entrance of women in the labor market carries implications for the organization and structure of family functioning, leading to the proposition of new settings, family arrangements with direct interference in the mother-child and family dynamics.A major challenge for women is to reconcile time for household chores, academic, external work and be able to stay with their children in order to be able establish an affective bond and harmonious.In this sense, one can say that in married life the roles played by man and woman has been increasingly confused and that family configuration has been designed differently from the traditional family structure as well as the mother-child relationship is also touched by these events.

A entrada da mulher no âmbito do trabalho traz repercussões na organização e na estrutura de funcionamento familiar, levando à proposição de novas configurações, arranjos familiares com interferências diretas na relação mãefilho e na dinâmica familiar.Um dos principais desafios para a mulher está em conciliar tempo para tarefas domésticas, acadêmicas, trabalho externo e poder permanecer com os filhos,de forma a ser possível estabelecer um vínculo afetivo harmonioso e consistente. Nesse sentido, é possível dizer que na vida conjugal os papéis desempenhados pelo homem e pela mulher tem se confundido cada vez mais e que a configuração familiar tem-se delineado diferentemente da estrutura familiar tradicional assim como a relação mãe-filho também é tocada por essas vicissitudes.
Keywords: Woman; Labor market; Mother-child relationship; Family; Mulher; Mercado de trabalho; Relação mãe-filho; Família